Luminescent Conjugated Oligothiophenes for Sensitive Fluorescent Assignment of Protein Inclusion Bodies. Issue 5 (28th February 2013) - Klingstedt, Therése; Blechschmidt, Cristiane; Nogalska, Anna; Prokop, Stefan; Häggqvist, Bo; Danielsson, Olof; Engel, W. King; Askanas, Valerie; Heppner, Frank L.; Nilsson, K. Peter R.
Abstract Small hydrophobic ligands identifying intracellular protein deposits are of great interest, as protein inclusion bodies are the pathological hallmark of several degenerative diseases. Here we report that fluorescent amyloid ligands, termed luminescent conjugated oligothiophenes (LCOs), rapidly and with high sensitivity detect protein inclusion bodies in skeletal muscle tissue from patients with sporadic inclusion body myositis (s‐IBM). LCOs having a conjugated backbone of at least five thiophene units emitted strong fluorescence upon binding, and showed co‐localization with proteins reported to accumulate in s‐IBM protein inclusion bodies. Compared with conventional amyloid ligands, LCOs identified a larger fraction of immunopositive inclusion bodies. When the conjugated thiophene backbone was extended with terminal carboxyl groups, the LCO revealed striking spectral differences between distinct protein inclusion bodies. We conclude that 1) LCOs are sensitive, rapid and powerful tools for identifying protein inclusion bodies and 2) LCOs identify a wider range of protein inclusion bodies than conventional amyloid ligands.